Decoupling the contributions of constituent layers to the strength and ductility of a multi-layered steel. (December 2016) - Seok, Moo-Young; Lee, Jung-A; Lee, Dong-Hyun; Ramamurty, Upadrasta; Nambu, Shoichi; Koseki, Toshihiko; Jang, Jae-il
Abstract: Multi-layered steel (MLS) consisting of alternating soft/ductile austenitic and hard/brittle martensitic stainless steel layers is a new class of hybrid material for structural application as it offers excellent combinations of strength and ductility. In this study, the contributions of each of the constituent layers to the overall strength and ductility of an MLS (having tensile strength > 1.4 GPa and ductility > 20%) were examined by recourse to nanoindentation experiments on each of them. By adapting two different indenter tip radii for the spherical nanoindentation experiments, constituent layers' stress-strain responses within the plastic regime were obtained and then compared with the macroscopic flow curve of the MLS that was obtained through tensile tests, to show that the strength contributions of the constituent steels to the global strength of MLS is as per the rule of mixtures. In order to examine the sources of tensile ductility of the MLS, sharp tip nanoindentation experiments were conducted on specimens extracted from tensile coupons that were subjected to predetermined plastic strains a priori . Results of these experiments show that the tensile failure occurs at a strain at which hardness of the austenitic layer, which is found to be dependent on the prior-plastic strain, is almost equal to the strain-independent hardness of the martensitic layer. The results are discussed in terms of martensitic transformation within austenitic layer and the role of the mechanical environment change imposed by the neighboring martensite layers on it. Graphical abstract: Image 1